PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA DOSEN MELALUI MEDIASI KEPUASAN KERJA - Sufiyati Sufiyati; Sofia Prima Dewi; Merry Susanti (Jurnal Bina Manajemen, 2022)
This study aims to find the relationship between leadership style, job satisfaction, and lecturer performance. The questionnaire was distributed to 55 lecturers at the Faculty of Economics and Business using convenience sampling. The data were processed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that leadership style has a positive effect on job satisfaction, job satisfaction has a positive effect on lecturer performance, leadership style has a negative effect lecturer performance, and leadership style has a positive effect on lecturer performance through job satisfaction.